Resources availability and COVID-19 mortality among US counties - Epané, Josué Patien; Zengul, Ferhat; Ramamonjiarivelo, Zo; McRoy, Luceta; Weech-Maldonado, Robert (Frontiers in Public Health, 2023)
The COVID-19 was declared a pandemic by WHO on 03/2020 has claimed millions of lives worldwide. The US leads all countries in COVID-19-related deaths. Individual level (preexisting conditions and demographics) and county-level (availability of resources) factors have been attributed to increased risk of COVID-19-related deaths. This study builds on previous studies to assess the relationship between county-level resources and COVID-19 mortality among 2,438 US counties. We merged 2019 data from AHA, AHRF, and USA FACTS. The dependent variable was the total number of COVID-19-related deaths. Independent variables included county-level resources: 1) hospital staffing levels (FTE RNs, hospitalists, and intensivists) per 10,000 population; 2) hospital capacity (occupancy rate, proportion of teaching hospitals, and number of airborne infection control rooms per 10,000 population); and 3) macroeconomic resources (per capita income and location (urban/rural)). We controlled for population 65+, racial/ethnic minority, and COVID-19 deaths per 1,000 population. A negative binomial regression was used. Hospital staffing per 10,000 population (FTE RN (IRR=0.9976; p≤0.01), FTE hospitalists (IRR=0.9362; p≤0.01), and FTE intensivists (IRR=0.6064; p≤0.0001)) was associated with lower COVID-19-related deaths. Hospital occupancy rate, proportion of teaching hospitals, and total number of airborne infection control rooms per 10,000 population were positively associated with COVID-19-related deaths. Per capita income and being in an urban county were positively associated with COVID-19-related deaths. Finally, the proportion of 65+, racial/ethnic minorities, and the number of cases were positively associated with COVID-19-related deaths. Our findings suggest that focusing on maintaining adequate hospital staffing could improve COVID-19 mortality.